Integrating Person-Centered Therapy Counseling in Pesantren: Nyai Zainiyah As’ad’s Response to Globalization Challenges / Mengintegrasikan Konseling Person-Centered Therapy di Pesantren: Respons Nyai Zainiyah As’ad terhadap Tantangan Globalisasi - Arifin, Samsul (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2025)
Pesantren education plays a crucial role in shaping students' character, yet it faces challenges in the era of globalization, such as moral crises and rising individualism. The integration of Person-Centered Therapy (PCT), developed by Carl Rogers—which emphasizes empathy and unconditional positive regard—is considered compatible with pesantren values. This study explores the thought and educational practice of Nyai Zainiyah As’ad in adapting PCT to build students’ character. Using a hermeneutic-ethnographic approach, it analyzes educational texts and pesantren practices through observation and in-depth interviews. The findings reveal that Nyai Zainiyah’s educational model emphasizes empathy, simplicity, honesty, and independence, while encouraging critical thinking and spiritual growth. Despite structural challenges such as hierarchical authority, integrating PCT remains feasible through humanistic approaches and Islamic values like ihsan and ukhuwah. This model offers both theoretical and practical contributions to character education, proposing an adaptive, holistic, and context-based framework for nurturing morally grounded and intellectually resilient individuals in the globalized era.